Endovascular Coiling Embolization in Direct Carotid Cavernous Fistula - Yulika Harniza; Syntia Nusanti; Jacub Pandelaki (Majalah Oftalmologi Indonesia, 2020)
Background: Carotid cavernous fistula (CCF) is a rare life-threatening. Rapid endovascular technical development has provided as a safe and effective treatment strategy for direct CCF (DCCF). Coiling treatment is a promising endovascular procedures solution in DCCF. Method: A comprehensive PubMed, Clinical key, and Ophthalmology database search was conducted using appropriate keywords (direct carotid cavernous fistula, endovascular treatment, embolization, and coil). Inclusion criteria was only article in English. Results: Nine studies (8 case series and 1 cohort study) were found suitable. From these results, endovascular coiling treatment can close the fistula with radiological evaluation and improvement in clinical symptoms in most of studies (90% and 88%, respectively). Post-operative and long-term complication were reported in some studies. Conclusion: Efficacy of endovascular coiling embolization appears promising in management of DCCF. There were no intra-operative complications and post-operative complications, such as unraveled micro-coil. The recurrence fistula rate of 4% is common in fistulas with larger tears associated with a larger CCF.